PERSEPSI PASIEN TERHADAP KUALITAS PELAYANAN RUMAH SAKIT UMUM DAERAH (RSUD) BANYUDONO KABUPATEN BOYOLALI PROVINSI JAWA TENGAH - -, Suwardi (Transformasi, 2011)
Abstract Service quality become the strategic pillar for hospital property of local government RSUD Bayudono. Service quality represent the approach emphasizing perception of service consumer. Five demensi of service measurement at this research is consisted by the reliability; responsivenness; assurance; empathy; and tangible. The five dimension this research conclude that quality of service of RSUD Bayudono pursuant to perception of client tend to the goodness. Â  Kata Kunci : Kualitas; Pelayanan; Persepsi; dan Rumah Sakit